Health risk factors among the older European populations: Personal and country effects - Teresa García-Mu\~noz; Shoshana Neuman; Tzahi Neuman (Bar-Ilan University, Department of Economics, 2014)
It is now common to use the individual's self-assessed-health-status (SAHS), which expresses her/his holistic 'internal' view, as a measure of health. The use of SAHS is supported by numerous studies that show that SAHS is a better predictor of mortality and morbidity than medical records. The 2011 wave of the rich Survey of Health Aging and Retirement Europe (SHARE) is used for the exploration of the full spectrum of factors behind the health-status in 16 European countries, using 23,800 observations. Special emphasis is given to the examination of behavioral risk factors (smoking, alcohol consumption and obesity) - both at the individual and country levels. The main findings are: (i) the estimation of self-assessed-health-status regressions provides clear evidence of the effects of the three behavioral risk factor on the individual's subjective rating of her/his health status, beyond and above the obvious effects of health conditions and of socio-economic personal variables; (ii) the second, more innovative, finding is related to the effects of country-specific risk factors (country-level measures of smoking, obesity, and alcohol consumption) on the subjective-health of the residents, beyond and above those of the personal characteristics. Adapting the technique presented in Oswald and Wu (2010), country effects derived from the SAHS regression are examined for correlations with a set of objective country macro measures. They include: share of smokers on a daily/regular basis; alcohol consumption (per-capita liters per year); share of obese individuals in the country. It appears that country-level smoking and obesity affect negatively aggregate country SAHS, while alcohol consumption has no effect. It is therefore not only 'who you are' that affects the subjective rating of health, but also 'in which country you live'. Overall, our findings indicate that what is true for the individual is also true for the country as a whole: both individual and country-level (obesity and smoking) risk factors affect subjective-health and the two levels of behavioral risks accumulate and reinforce the subjective-health assessment. This seems to be at odds with the 'Easterlin Paradox' that emphasizes within country individual effects and denies cross-country effects, and suggests the economic cost-effectiveness of preventive obesity and smoking treatment.
Keywords: 330